The Relationship Between Knowledge, Attitude And Hand Washing Behavior With Recurrent Typhoid Fever In Puskesmas Bojong Rawalumbu Bekasi 2019 - Simamora, Rotua Suriany (Jurnal Ayurveda Medistra, 2020)
Background : Typhoid fever is a disease that attacks the small intestine. This disease is influenced by the environment, clean and healthy lifestyle, self hygiene. Hand washing is one of the most effective and often overlooked ways to prevent the spreas of various types of infections and diseases both at home, workplace and hospital. Purpose : This study aims to determine the relationship of knowledge, attitudes and handwashing behavior with recurrent typhoid fever in puskesmas bojong rawalumbu bekasi. Method : This research method used descriptive analytic correlation design with cross sectional study approach. Results of research: There is no correlation between knowledge and hand washing attitudes with recurrent typhoid events but there is a significant relationship between handwashing behavior and the incidence of recurrent typhoid fever in puskesmas bojong rawalumbu with P Value 0,006